Transformasi Digital UMKM: Strategi Branding dan Optimalisasi Marketplace bagi Pelaku Usaha Nugget - Rifai, Anwar; Wardani, Hadidtyo Wisnu; Andini, Prita (Welfare : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to enhance the digital skills of small and medium-sized enterprises (SMEs) in online marketing, social media usage, marketplaces, and product branding. The training was conducted by inviting experts in digital marketing and branding to provide relevant materials for SMEs. The method used is Service Learning, which integrates academic theory with direct community engagement. The activity was attended by SME owners in the nugget production industry and took place at the SME location in Paninggilan. Evaluation results through pretest and posttest showed an increase in participants' knowledge, with an average gain score of 32.5%. Statistical analysis using paired t-test revealed a significant difference between pretest and posttest scores (p-value = 7.34 × 10^(-9)), indicating the effectiveness of the training in improving participants' understanding. Based on these results, it is recommended to expand this training program to more SMEs in other areas and further develop it by adding content related to the latest digital technologies. This training is expected to contribute to enhancing the competitiveness of SMEs in the digital marketplace and drive a broader digital transformation in the SME sector.